Byzantium and Alexander the Great: A Convergence of Interests - Prandi, Luisa (Anabasis. Studia Classica et Orientalia, 2018)
The present paper focuses on a small detail in Arrian’s narrative concerning the Balkan campaign of Alexander (335 BC). The presence of a fleet leaving Byzantium to meet the king along the river Istros suggests a coherent frame to better understand the politics of the Greek city, which was concerned with the menace of the barbarians, and had to face strategic plans of Alexander. The alliance between the Macedonian king and Byzantium cannot be regarded as an episodic phenomenon.